Exercise training prevents the exaggerated exercise pressor reflex in rats with chronic heart failure - Wang, Han-Jun (American Physiological Society, 2010)
An exaggerated exercise pressor reflex (EPR) occurs in the chronic heart failure (CHF) state, which contributes to exercise intolerance and excessive sympathoexcitation during exercise. Exercise training (ExT) improves abnormal cardiovascular reflexes in CHF. Whether ExT can normalize the exaggerated EPR function remains to be determined. This study was designed to investigate the effects of ExT on the EPR and on the mechanical or metabolic components of this reflex in sham-operated and CHF rats. The EPR was activated by static contraction induced by electrical stimulation of L(4)/L(5) ventral roots. The afferent fibers associated with the mechanoreflex and metaboreflex were activated by passive stretch and hindlimb arterial injection of capsaicin (0.1 and 1 μg/kg, 0.2 ml), respectively. Heart rate, blood pressure, and sympathoexcitatory responses during the activation of these reflexes were compared in sham + sedentary (Sed), sham + ExT, CHF + Sed, and CHF + ExT rats. Compared with sham + Sed rats, CHF + Sed rats exhibited exaggerated heart rate and pressor and sympathoexcitatory responses to either static contraction or passive stretch, whereas the cardiovascular responses to injection of capsaicin were blunted. Eight to ten weeks of ExT normalized the exaggerated responses induced by static contraction or passive stretch and partially improved the blunted responses due to intra-arterial capsaicin in CHF rats. ExT had no significant effect on the EPR and mechanoreflex and metaboreflex functions in sham rats. These findings suggest a potential therapeutic role for ExT in minimizing arterial pressure and sympathetic outflow following activation of the EPR in the CHF state.